The Influence of Society in Committing Suicide in The Midnight Library Novel by Matt Haig - Novi Fatati Syihamun Nahdiyah (Lakon : Jurnal Kajian Sastra dan Budaya, 2022)
People believe committing suicide is caused by an individual’s mental disorder. Therefore, suicide is identified as the individual's responsibility. However, in the theory of suicide by Emile Durkheim, he offers a different perspective on committing suicide. Durkheim argues society has influenced the individual's life by committing suicide. According to the phenomena, this study aims to identify the social factors that influence Nora to suicide in the novel The Midnight Library by Matt Haig. The study uses a descriptive analysis method and applies the theory of suicide by Emile Durkheim. The researcher identifies two factors that influenced Nora to suicide, namely egoistic and fatalistic. The people around Nora (family, friends, and partner) do not have a good relationship with her. On the other hand, the standardization or ideology of society put more and more pressure on Nora’s life. These two social factors influence Nora to decide to end her life.